Scribal Education in Ancient Israel: The Old Hebrew Epigraphic Evidence - Rollston, Christopher A. (Bulletin of ASOR, 2006)
There has been substantial discussion about the presence of "schools" in Iron Age Israel (that is, Israel and Judah), with some scholars affirming that there were schools and some positing that there is no cogent evidence for them. Within this article, the Iron Age Old Hebrew epigraphic evidence is analyzed. Based on the nature of the palaeographic evidence, the orthnographic evidence, and the use of hieratic numerals, it is here argued that formal, standardized scribal education was a component of ancient Israelite society during Iron II. Of course, some have posited that becoming proficient in the Old Hebrew writing system was so facile that there was no need for formal, standardized education. However, modern empirical studies of the length of time required for proficiency in a first alphabetic writing demonstrate that the field has been too sanguine about the pace of learning the Old Hebrew writing system.